Demographic changes, educational improvements, and earnings in Brazil and Mexico - Ernesto F. L. Amaral; Bernardo L. Queiroz; Júlia A. Calazans (IZA Journal of Labor & Development, 2015)
This paper estimates the association of demographic and educational changes with earnings and returns to schooling of male workers in Brazil and Mexico. Our analysis takes into account demographic, educational, and economic variations within each country over time, using Demographic Censuses microdata from Brazil and Mexico. Results suggest that demographic and educational transitions are correlated with earnings and returns to education. Proportions of people in age-education groups tend to have negative associations with aggregated earnings. Workers with secondary education completed experience negative effects on their earnings by having lower education than university graduates (education effect) and by representing a bigger share of the population than males with university education completed (cohort size effect). The negative correlations of cohort size have been decreasing in magnitude over time. We also find that the concentration of skilled labor in specific locations has positive associations with individual earnings and that they are greater than those observed in more developed countries. Moreover, in Brazil and Mexico, these effects are observed throughout the income distribution, contrary to what is observed in studies for the United States.
Keywords: I2; J1; 330; Demographic transition; Education transition; Cohort size; Earnings; Labor Markets; Brazil; Mexico